Membrane process optimization for carbon capture - Norfamila, Che Mat; Lipscomb, Glenn Glenn (Elsevier Ltd, 2017)
The utilization of membrane technology in post-combustion applications is hindered by low CO2 feed partial pressure in the flue gas stream. In order to meet the separation targets of 90% CO2 recovery, 95% or higher CO2 purity, and a Levelized Cost of Electricity (LCOE) increase of less than 35%, Membrane Technology and Research, Inc. (MTR) (Merkel et al., 2010) has proposed the use of the boiler air feed as a sweep stream to increase the CO2 concentration in the flue gas and partial pressure driving force for permeation without additional compression or vacuum. Such a design significantly reduces capture cost but leads to a detrimental reduction in the O2 concentration of the feed air to the boiler. The transport properties and operating pressures of the membrane stages are optimized in this study. Membrane CO2/N2 selectivity is varied over a broad range encompassing the values considered by MTR. Membrane CO2 permeability is varied with selectivity according to the variation anticipated by the upper bound of the Robeson plot for CO2 and N2. Membrane CO2 permeance is calculated assuming membranes can be fabricated with an effective thickness of 0.1 μm. Additionally, the two stages may utilize different membrane materials. The feed and permeate pressures also are varied over ranges encompassing the values proposed by MTR. The optimization space of membrane properties and operating conditions is scanned globally to determine the process design that minimizes LCOE. The O2 concentration to the boiler is evaluated during the optimization process and can be used to constrain viable alternatives. The results indicate a fairly broad range of membrane properties can yield comparable LCOE near the minimum. The optimal operating pressure range is somewhat narrower. The minimum allowable O2 concentration constrains viable designs significantly and is critical to process economics.